BUSINESS FEASIBILITY STUDY TO PROMOTE LOCAL FASHION (A CASE STUDY ON GAYAKU) - Wijaya, Septihani Michella; Jane, Jennie; Wijaya, Andi (International Journal of Application on Economics and Business, 2023)
In recent years, business in all fields have faced increasingly global competition. In 2022, the fashion industry is growing and is seen as an industry with the potential to support economic recovery. At present, clothing is not only a primary demand, but also an artistic demand. Gayaku is a fashion product with a design of Indonesian culture as theme. Gayaku products are made of high-quality textile materials, so the clothes are very comfortable to wear, the material is not easy to stretch, and the silk screen will not break quickly, so that it can be used for a long time. Gayaku has a modern and contemporary design concept. In order to better understand market efforts and developments, Gayaku conducts a SWOT analysis, market potential analysis, and business risk analysis. The research method in this study is Qualitative research methods aim to explain a phenomenon in depth and are carried out by collecting data as deeply as possible. Gayaku also has a marketing plan to keep the business running. In order to compete with well-known and brand-name brands, Gayaku will carry out a series of marketing strategies, namely customer relations, activation of social media platforms, endorsement of key opinion leaders, digital campaigns, bajoe E-commerce, and special events.